Mediador cultural: profissionalização e precarização das condições de trabalho - Silva, Cintia Maria da [UNESP] (2017)
The purpose of this paper is to analyse how the work conditions offered by the cultural equipments of the City of São Paulo interpose into the educational practice of the workers of cultural mediation, who works in art exhibitions. The theoretical foundations are divided in two axis: education and cultural mediation (FREIRE, SAVIANI, VYGOTSKY; BARBOSA, DARRAS, HOOPER-GRENHILL, MARTINS); Neoliberalism and its implication in culture (HARVEY, BRESSER-PEREIRA). It was considered the transformations of historical context, political and social in Brazil from the 1990s (ampliation of tax incentive law, outsourcing and privatization of the work, big exhibitions) to define how does this impacted in the quality of the pedagogical actions offered by the cultural equipments. For this purpose, nine coordinators of three kinds of institutions of cultural equipments were interviewed: private institutions, social organizations and outsourcing companies. From the collected data, it was elaborated a plan of the work morphology (ANTUNES) of the cultural mediator worker: contracting regime, salary remuneration and benefits, working journeys, days off, expertise and continuing education, career plan and symbolical valorization. It was considered the Brazilian occupations classification, which the work of the cultural mediator it’s not a regulated profession and because of that, the professionalization it turns out to be a complexed case to be analysed. Therefore, the precarization of the work conditions (ANTUNES, ALVES) it can’t be here understood as a loss of labor rights because it was never considered as a work, and so never had this rights - as well needing to be discussed.